2004
DOI: 10.1007/s00535-003-1386-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gap junction protein connexin32 in chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma

Abstract: These findings suggest the possibility that changes in both the amount and the distribution of Cx32 may be implicated in human hepatocarcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 23 publications
3
52
0
7
Order By: Relevance
“…Since both liver development and cancer are associated with clear-cut changes in connexin expression, these proteins may form a novel set of clinical diagnostic indicators and therapeutic targets (Nakashima et al, 2004;Nakata et al, 1996;Yamaoka et al, 2000). Specifi cally, connexins could be used as biomarkers of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both liver development and cancer are associated with clear-cut changes in connexin expression, these proteins may form a novel set of clinical diagnostic indicators and therapeutic targets (Nakashima et al, 2004;Nakata et al, 1996;Yamaoka et al, 2000). Specifi cally, connexins could be used as biomarkers of disease.…”
Section: Discussionmentioning
confidence: 99%
“…hepatitis, fi brosis and cirrhosis) as well as during hepatotoxicity (Nakashima et al, 2004;Nakata et al, 1996;Yamaoka et al, 2000). This is equally refl ected at the posttranscriptional level and is caused by increased degradation of Cx32 mRNA molecules (Gingalewski et al, 1996).…”
Section: Connexins and Alterations In The Liver Differentiation Statusmentioning
confidence: 99%
“…Cxs have been previously reported in various types of malignant tumors, including breast, liver, colon, and esophageal tumors [5][6][7][8][9][10]. A decrease or loss of Cxs expression has also been reported [6,11].…”
mentioning
confidence: 90%
“…In addition, Conklin et al [6] reported that Cx43 is downregulated at various stages of breast cancer progression, including ductal carcinomas in situ, infiltrating ductal carcinoma and infiltrating lobular carcinomas. Although some reports have implicated reduced or absent Cx expression in cancer progression, others have suggested that altered subcellular localization of Cx32, specifically, intracytoplasmic expression, is involved [7][8][9]. Generally Cx is distributed primarily along membranes of normal cells, but in hepatocellular carcinoma Cx32 is mostly detected in both the cytoplasm and on the cell membranes of tumor cells [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation